Young Children Can Be Taught Basic Natural Selection Using a Picture-Storybook Intervention. (April 2014) - Kelemen, Deborah; Emmons, Natalie A.; Seston Schillaci, Rebecca; Ganea, Patricia A.
Adaptation by natural selection is a core mechanism of evolution. It is also one of the most widely misunderstood scientific processes. Misconceptions are rooted in cognitive biases found in preschoolers, yet concerns about complexity mean that adaptation by natural selection is generally not comprehensively taught until adolescence. This is long after untutored theoretical misunderstandings are likely to have become entrenched. In a novel approach, we explored 5- to 8-year-olds' capacities to learn a basic but theoretically coherent mechanistic explanation of adaptation through a custom storybook intervention. Experiment 1 showed that children understood the population-based logic of natural selection and also generalized it. Furthermore, learning endured 3 months later. Experiment 2 replicated these results and showed that children understood and applied an even more nuanced mechanistic causal explanation. The findings demonstrate that, contrary to conventional educational wisdom, basic natural selection is teachable in early childhood. Theory-driven interventions using picture storybooks with rich explanatory structure are beneficial.